Utility and Usability of the Rapid Assessment of Hospital Procurement Barriers in Donation (RAPiD) as a Tool for OPO Hospital Development Staff. (September 2016) - Alolod, Gerard P.; Traino, Heather M.; Siminoff, Laura A.
Context: Few systematic assessment tools are available to organ procurement organizations (OPOs) for evaluating donation climates of hospitals in their donation service areas (DSAs). The Rapid Assessment of hospital Procurement barriers in Donation (RAPiD) was developed for OPO hospital development staff to assess the organ donation climate of hospitals. Objective: To implement a national test of the RAPiD to examine its efficacy and usability by OPO hospital development staff. Design: Two-arm randomized design, comparing implementation of RAPiD protocol between qualitatively trained researchers (n = 7) and OPO hospital development staff (n = 24); all evaluators received the same training assessments of high-yield hospitals. Setting: A total of 77 hospitals in DSAs of 8 OPOs. Participants: A total of 2552 health-care providers (HCPs) in high organ donor potential units. Main Outcome Measures: Twenty-four donation-related attitudes, knowledge, and behaviors. Results: More HCPs interviewed in the autonomous condition were positive toward the concept of organ donation. However, HCPs in the assisted condition were more candid about and critical of the OPO. As for knowledge, fewer HCPs in the autonomous condition reported familiarity with the donation process, need for donors, and generally accepted timely referral criteria. With respect to behaviors, more respondents in the autonomous condition reported frequent or occasional contact with the OPO and routine or occasional referral criteria use. Due to issues of bias, inadequate research experience, conflicts of interest, and ongoing OPO hospital development initiatives, the RAPiD's usability by OPO-based hospital development staff is questionable and not recommended in its current form. A next generation of the RAPiD is described for future consideration.